IMPACT OF COLOUR PSYCHOLOGY ON STUDENTS’ EMOTIONAL WELL-BEING - Emaikwu, Owoicholohi Sam-Favour; Omale, Reuben (Universitas Ciputra Surabaya, 2026)
Colour can influence perception, mood, and behaviour. It may also affect how students behave in academic settings. This paper examined the effects of classroom colour schemes on students' moods, concentration, and learning experiences at the Federal University of Technology, Akure (FUTA). A mixed methods approach was used. Quantitative data were gathered through a survey of 250 responses. Qualitative data were gathered from students' comments on their narratives. The results showed that neutral and tranquil colours, such as cream, white, grey, and blue, were more closely associated with relaxation and concentration. Conversely, bright colours, including red and yellow, were often linked to stress and distraction. The research revealed that the effect of colours in a learning space depends on how they are paired with both natural and artificial light, as well as other factors such as furniture design. Students' emotional responses were also influenced by cultural and personal perceptions of colours, especially red, black, and white. These findings contribute to the literature by demonstrating how colour, lighting, and furniture together affect students' academic activities. Based on the results, the researchers recommend that universities use neutral, balanced colour schemes, proper lighting, and sensitive classroom design to foster comfort, concentration, and learning.